Creating shared value through open innovation approaches: Opportunities and challenges for corporate sustainability - Camilleri, Mark Anthony; Troise, Ciro; Strazzullo, Serena; Bresciani, Stefano (Business strategy and the environment, 2023)
To date, few researchers have linked open innovation approaches with triple bottom line corporate sustainability objectives in terms of economic, social, and environmental performance. A systematic review suggests that the businesses' collaborative relationships with external consultants or organizations can increase their competitive advantage, as external stakeholders could assist them in the development of sustainable innovations, diversification into different markets, and in the generation of new revenue streams. At the same time, they can support them in addressing numerous deficits in society. On the other hand, this contribution implies that an organizational culture that promotes open innovation approaches could expose practitioners to risks and uncertainties, like revealing sensitive information to outsiders, among others. In reality, it may prove difficult for the businesses to trust new partners, as they are not subject to their organizations' codes of conduct, rules, and regulations.